2021
DOI: 10.18494/sam.2021.3323
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and Scintillation Properties of Tb:GdTaO4 Crystals

Abstract: Tb-doped GdTaO 4 crystals were synthesized to investigate their photoluminescence and scintillation properties. Tb:GdTaO 4 exhibits photo-and radioluminescence characterized by several sharp peaks due to 4f-4f transitions of Tb 3+ . The photo-and radioluminescence decay time constants are 500-900 μs. The values become short with increasing Tb concentration and are typical for the 4f-4f transitions of Tb 3+ . From the quantum yield (QY), radioluminescence spectra, and pulse height under 137 Cs γ-rays, the 1% Tb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…(18,19) As further advantages, the perovskite crystals can be grown at a low cost owing to a low-temperature process in comparison with most inorganic scintillators synthesized by melt-growth methods (e.g., Czochralski, Bridgeman, and Floating Zone methods). (6,(20)(21)(22) According to a previous study, (C 6 H 5 C 2 H 4 NH 3 ) 2 PbBr 4 has shown high LY (14000 ph/MeV) and fast scintillation decay time (11 ns). (23) On the basis of this study, various types of lead bromide-based organic-inorganic hybrid perovskite-type compounds have been continuously explored, (24)(25)(26)(27)(28) whereas there have been only a few reports on the scintillation properties of other halide-based organic-inorganic hybrid perovskite-type compounds (e.g., lead chloride-and iodide-based ones).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…(18,19) As further advantages, the perovskite crystals can be grown at a low cost owing to a low-temperature process in comparison with most inorganic scintillators synthesized by melt-growth methods (e.g., Czochralski, Bridgeman, and Floating Zone methods). (6,(20)(21)(22) According to a previous study, (C 6 H 5 C 2 H 4 NH 3 ) 2 PbBr 4 has shown high LY (14000 ph/MeV) and fast scintillation decay time (11 ns). (23) On the basis of this study, various types of lead bromide-based organic-inorganic hybrid perovskite-type compounds have been continuously explored, (24)(25)(26)(27)(28) whereas there have been only a few reports on the scintillation properties of other halide-based organic-inorganic hybrid perovskite-type compounds (e.g., lead chloride-and iodide-based ones).…”
Section: Introductionmentioning
confidence: 93%
“…For X-and γ-ray detector uses, the following properties are generally required: high light yields (LY), large effective atomic number (Z eff ), high density, short scintillation decay time, low afterglow, and low fabrication costs. (5,6) Applications of scintillators cover wide fields such as medical imaging, (7) space explorations, (8) well logging, (9) and inspection equipment for security. (10) The required properties are varied.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused on a translucent ceramic, (22)(23)(24) a new material form of scintillators that can be used to enhance lattice-defect luminescence. Translucent ceramics have more lattice defects than other material forms such as single crystals, (25,26) which are generally used as scintillators; thus, ZnO translucent ceramics may have enhanced LY. Moreover, it was previously reported that the introduction of Li increased the concentration of lattice defects and enhanced the photoluminescence (PL) properties of ZnO films.…”
Section: Introductionmentioning
confidence: 99%
“…(3) In general, an X-or γ-ray scintillator requires a high scintillation light yield (LY), short decay time, high energy resolution, high density, large effective atomic number, and low afterglow. Therefore, there has been continuous R&D to develop more desirable materials in single crystal, (4)(5)(6)(7)(8)(9)(10)(11)(12) ceramic, (13)(14)(15) glass, (16)(17)(18)(19) and liquid forms. (20)(21)(22) A high density and a large effective atomic number are important for obtaining large cross sections against X-and γ-rays; (23) thus, pyrochlore rare-earth hafnates (RE 2 Hf 2 O 7 , RE: rare earth) are potential scintillators with high density (9.0 and 9.7 g/cm 3 for Gd 2 Hf 2 O 7 and Lu 2 Hf 2 O 7 , respectively (24) ) and large effective atomic numbers (66-69).…”
Section: Introductionmentioning
confidence: 99%